MEASUREMENT OF CARBON MONOXIDE EMISSIONS FROM VEHICLES EXHAUST PIPE USING PORTABLE GAS DETECTOR - Hassoon, H.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Carbon monoxide (CO) contamination represents a major global concern. This study aimed to detect the concentration of CO, emitted from various vehicles exhausters which are important contributors in deteriorating air quality. The data was collected throughout the heavy parking period at Al- Jadyria campus in Baghdad University. The vehicles were classified into two main groups according to the type of gasoline they are filled with; including premium leaded and leaded free gasoline (PLG and LFG respectively), as well as engine size, odometer, brand and model. Seven low duty vehicles for each engine size (<1.6 to >2.0) liter were selected randomly. A portable gas detector type (Altair® 4X) was used to measure exhausted emission of CO during idle mode. The results showed that high mean levels of CO (206.111–939) ppm were observed within vehicles filled with PLG. In contrast, the vehicles filled with LFG had been detected with an observable decline (9.5714–21.5714) ppm. Also, a significant difference in gas concentration between fuel types was observed within various engine groups. This study recommended controlling these emissions and raising the concern of the government about the gasoline quality due to their adverse impact on human health and environment.